Process selection and optimization of cellulose extraction from palm kernel using response surface methodology - Farm, Yan Yan (2009)
Palm kernel cake (PKC) as one of the abundant high cellulose content oil palm by products. Hence, PKC is significantly considered as potential resources for cellulose production. Numerous treatments have been developed in efforts to extract cellulose from wood and non-wood sources. However, efficient separation of cellulose from non-wood sources still constitutes as one of the major obstacles to extensive utilization of cellulose in industry. The present research was undertaken to select the best cellulose extraction method for PKC and followed by optimization of the selected method. The extractions of PKC cellulose were compared with the established pretreatments (hydrothermal treatment and alkali treatment) and three different delignification techniques (Organolsolv, Liquid phase oxidation (LPO) and Acidic sodium chlorite). Both of the treated residues were verified by FTIR as cellulose, yet with some contamination. Hence, process selection was conducted to select the best cellulose extraction method. LPO with 77 minutes of alkali treatment was selected as the best cellulose extraction process. Next, it was followed by the optimization of the LPO. The optimized conditions are ratio of Hâ‚‚Oâ‚‚ to PKM at 10.30 (g/g), 149min of reaction time, reaction temperature at 65â°C and 12.5mg of FeSOâ‚„ as catalyst for 24% of hemicellulose removed, 16% of yield cellulose based on the dry basis of PKC and 90.31% cellulose purity. Preidentification size of PKC cellulose using GPC was carried out. It was discovered that PKC cellulose is a -cellulose with an intermediate molecular weight. For the analysis of organic acids content, formic acid and acetic acid formed as the dominant acids in the solution. LPO with alkali treatment is not only a green and efficient cellulose extraction method, it also produce valuable by-products. Hence, extraction of cellulose from palm kernel cake using LPO with alkali treatment is a great potential for new industrial process.